The transcription factor STAT5 catalyzes Mannich ligation reactions yielding inhibitors of leukemic cell proliferation - Ee Lin Wong (Nature Portfolio, 2019)
The oncogene STAT5 is involved in cancer cell proliferation. Here, the authors use STAT5 protein to assemble its own small molecule inhibitors via Mannich ligation (three-component-reactions) and show that the resultant ligands can inhibit the proliferation of cancer cells in a mouse model.